Two-Phase Conceptual Framework of Phosphatase Activity and Phosphorus Bioavailability - Manzoor, Aamir; Dippold, Michaela A.; Loeppmann, Sebastian; Blagodatskaya, Evgenia (Frontiers in Plant Science, 2022)
The activity of extracellular phosphatases is a dynamic process controlled by both plant roots and microorganisms, which is responsible for the mineralization of soil phosphorus (P). Plants regulate the availability of soil P through the release of root mucilage and the exudation of low molecular weight organic acids (LMWOAs). Mucilage increases soil hydraulic conductivity as well as pore connectivity, both of which are associated with increased phosphatase activity. The LMWOAs, in turn, stimulate the mineralization of soil P through their synergistic effects of acidification, chelation, and exchange reactions. This article reviews the catalytic properties of extracellular phosphatases and their interactions with the rhizosphere interfaces. We observed a biphasic effect of root metabolic products on extracellular phosphatases, which notably altered their catalytic mechanism. In accordance with the proposed conceptual framework, soil P is acquired by both plants and microorganisms in a coupled manner that is characterized by the exudation of their metabolic products. As a consequence of inactive or reduced root exudation, plants recycle P through adsorption on the soil matrix, thereby reducing the rhizosphere phosphatase activity. The two–phase conceptual framework might assist in understanding P–acquisition (substrate turnover) and P–restoration (phosphatase adsorption by soil) in various terrestrial ecosystems.